Food safety and hygiene practices of streed food vendors at gate two vending site at the University of Limpopo, Turfloop Campus, South Africa - Tleane, Ditsebe Marcia Rosina (My University, 2020)
Background: Street food vending has become a common means of providing traditional, known and convenient meals to communal eating. It has also become a growing portent as a means of job creation and as a survival mechanism to many affected by job creation decline. Suggestion: There is an influx of food vendors at Gate 2 of the University of Limpopo and there is a need to investigate both the hygiene and safety measures taken by the vendors and the environment they operate in. Methods: The purpose of the study was to observe and identify food safety and hygiene practices by the street vendors. An observational descriptive cross sectional study design and a convenience sampling technique were used as research designs and sampling methods. A questionnaire on food safety and hygiene was used to collect data. Results: The study revealed that all of the street vendors have no form of food safety and hygiene training. The vendors also highlighted the fact that over and above them having no food safety and hygiene knowledge, food safety and hygiene practices such as washing of hands frequently cannot be adhered to because of the time limitations they have to prepare and be ready for customers as quickly as possible. The vendors practise a mixed storage of raw and cooked food in the refrigerators within the refrigerators. Only 30% of the vendors wear protective hand gloves while preparing food. They have running water in the bathroom and on the premises but no soap is provided in the bathroom for hand washing. Conclusion: Even though street food is increasingly gaining popularity and accessibility based on affordability, traditional meals served and accessibility, food safety and hygiene still are a concern and a matter of alarm. Key words: food safety and hygiene, street food vendor, food poisoning, health hazards
Thesis (MPH.) -- University of Limpopo, 2020
Keywords: Food safety and hygiene; Street food vendor; Food poisoning; Health hazards; Street-food vendors; Street food; Food security